Algorithms for Lorenz System Manifold Computation - Meng Jia; Bing Wu (Institute of Advanced Engineering and Science, 2014)
A new algorithm is presented to compute both one dimensional stable and unstable manifolds of planar maps. It is proved that the gradient of the global manifold can be predicted by the known points on the manifold with a gradient prediction scheme and it can be used to locate the image or preimage of the new point quickly. The performance of the algorithm is demonstrated with hyper chaotic Lorenz system. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4740